Gene-Environment Interactions Relevant to Estrogen and Risk of Breast Cancer: Can Gene-Environment Interactions Be Detected Only among Candidate SNPs from Genome-Wide Association Studies? - Park, Jooyong; Choi, Ji-Yeob; Choi, Jaesung; Chung, Seokang; Song, Nan; Park, Sue K.; Han, Wonshik; Noh, Dong-Young; Ahn, Sei-Hyun; Lee, Jong Won; Kim, Mi Kyung; Jee, Sun Ha; et al. (Cancers, 2021)
Simple Summary
CRIS-Team WoS Importer:2021-06-04